On the Foundation of Multimedia Applications, Teaching "Information Technology in Construction" - A., Karimov A. (International Journal on Integrated Education, 2023)
This article provides recommendations for further improvement of teaching and learning methods using computer graphics programs in the process of teaching the subject” information technology in construction" using multimedia educational applications and ensuring efficiency.